PENGARUH LIKUIDITAS, PROFITABILITAS, DAN SOLVABILITAS TERHADAP OPINI AUDIT GOING CONCERN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE (2022 – 2024) - Nurhudabiah Putrijunita; Tutut Dewi Astuti (ITB AAS Indonesia Surakarta, 2026)
This study examines the effect of liquidity, profitability, and solvency on going concern audit opinions in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange during 2022–2024. Using a quantitative approach, secondary data from 20 companies (60 observations) were analyzed through multiple regression with SPSS.The results show that Current Ratio, Return on Assets, and Debt to Asset Ratio do not have a significant effect on going concern audit opinions, either partially or simultaneously. The model has low explanatory power, indicating that other factors outside the study variables are more influential in auditors’ decisions.In conclusion, liquidity, profitability, and solvency are not key determinants of going concern audit opinions in the sampled companies. Further research is recommended to include additional variables to improve analysis accuracy.